Histopathological differences between genders in patients with oral squamous cell carcinoma - Muradás Girardi, Fábio; Rubin Fuga, Giulia; Callai, Tássia; Fernandes Bianchi, Marina (Clinical and Biomedical Research, 2017)
Introduction: Oral cancer ranks fifth among the most frequent malignant tumors in men in Brazil. The incidence of this tumor among women has grown. It is still controversial whether gender can influence the outcome or the prognostic features of the disease. Objectives: To compare the histopathological features of oral squamous cell carcinomas between genders among patients undergoing surgical treatment in an oncological hospital of southern Brazil. Methods: Between 2007 and 2011, 404 patients underwent resection of malignant tumors of the oral cavity in the head and neck department of this institution. A subgroup of 209 previously untreated oral cavity squamous cell carcinoma cases was selected for comparative analysis. Results: In total, 68 participants were women and 141 were men. The tongue was the most common subsite in both genders. Men presented lower mean age and women presented tumors with smaller depth of invasion. Although among women it was observed a trend towards tumors with less aggressive characteristics, no other variable showed statistically significance. Conclusion: Women with oral tumors tend to present more superficial primary tumors and at a later age. Keywords: Oral neoplasms; carcinoma; squamous cell; prognosis